How highlighted utensils influence consumption in a dark setting. Issue 10 (3rd October 2018) - Stok, F. Marijn; Junghans, Astrid F.; de Ridder, Denise T. D.; Renner, Britta; Evers, Catharine
Abstract: Objective: Previous research has shown that people consume less food in the dark compared to normal vision conditions. While this effect is commonly attributed to increased attention to internal cues, it could also be caused by increased difficulty to maneuver in a dark setting. This study investigated this potential alternative explanation. Design: A 2 (dark versus normal vision setting) × 2 (highlighted versus non-highlighted utensils) between-subjects design was employed. Main outcome measures: Perceived difficulty of maneuvering and consumption of yoghurt were assessed as main outcome measures. Results: Participants consumed marginally less in dark compared to normal vision conditions, and experienced higher difficulty of maneuvering. Importantly, both effects were qualified by a significant interaction with highlighting, which increased consumption and reduced perceived difficulty compared to no highlights. Difficulty of maneuvering did not mediate the interactive effect of vision and highlighting on consumption. Conclusion: Difficulty to maneuver should be considered when investigating eating behaviour under dark conditions. In line with an embodied cognition account, results also reveal the necessity of visual information for interaction with objects in the environment and imply that detail-deprived object information may be sufficient for activation of the motor system.